The oral microbiome and human health - Yamashita, Yoshihisa; Takeshita, Toru (Journal of Oral Science, 2017)
In this brief review, we discuss our previous research on the relationship between the bacterial composition of salivary microbiota and periodontal disease. Analysis using a terminal restriction fragment length polymorphism method and an international comparison suggest that the predominance of the genera Prevotella and Veillonella in the salivary microbiota is attributable to periodontal disease conditions, and that the predominance of the genus Neisseria indicates healthy periodontal conditions. Furthermore, we recently used next-generation sequencing technology to perform a detailed large-scale analysis of the salivary microbiota. An important finding of that study was that high bacterial richness in the salivary microbiota was significantly associated with poor oral health, as indicated by decayed teeth, periodontitis, and poor oral hygiene. Another important result was that relative abundance of predominant bacteria in saliva was significantly associated with oral health-related conditions. Of the two different cohabiting groups of bacteria found in the salivary microbiota, a greater relative abundance of group I bacteria, which include Prevotella and Veillonella species, was associated with poor oral health, high body mass index, and old age. These findings suggest that the salivary microbiota reflects oral and systemic conditions.